Tradisi Peusijuek Sebagai Sarana Mediasi di Tengah Penegakan Syariat Islam di Aceh - Prayetno, Nanda Sekti; Qomaruzzaman, Bambang (TEMALI : Jurnal Pembangunan Sosial, 2021)
This study aims to find out how the peusijuek tradition as a means of mediation which is a relic of Hindu culture and deeds considered heretic so that it is not following Islamic law is still preserved in Kuta Baro District, Aceh Besar District, Aceh Province. This study uses a descriptive qualitative method, in which researchers directly obtain information from direct interviews and thorough literature review. In conducting this research, the researcher used the cultural functionalism theory, according to Malinowski. The theory of functionalism explains that the elements of culture have a relationship and reveals specific patterns or at least the reasons for these patterns to survive and be recognized by society. The peusijuek tradition as a means of mediation in the middle of Islamic law in Aceh has a significant role in society, because it has certain functions, namely as a carrier of prosperity, to expect blessings, maintain harmony between citizens, and preserve cultural heritage. Until now, peusijuek has become a social reality and has become an identity for the people of Aceh, especially the people in Kuta Baro District, Aceh Besar District.